2022
DOI: 10.1016/j.pedneo.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of SIRS, age-adapted pSOFA, and quick SOFA scoring systems for predicting outcomes in paediatric patients with sepsis: a meta-analysis

Abstract: Background: Sepsis is the leading cause of mortality in children. Several scoring systems are used to predict outcome and mortality for pediatric patients with sepsis, but how they compare to each other in terms of sensitivity and specificity is unclear. Methods: The systematic literature review was performed following PRISMA guidelines. Publically accessible search engines and study databases such as PubMed, CENTRAL (Cochrane Central Register of Controlled Trials), and Google Scholar were scanned for articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…1 Lastly, Sun et al reported a sensitivity of 83%, a specificity of 72%and a diagnostic accuracy of 85%. 18 While all the studies report that pSOFA has an adequate prediction ability in terms of mortality, there is a discrepancy within the results. We assume that this occurred because while other studies assessed patients at the time of admission, we conducted serial assessments, which improved diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 97%
“…1 Lastly, Sun et al reported a sensitivity of 83%, a specificity of 72%and a diagnostic accuracy of 85%. 18 While all the studies report that pSOFA has an adequate prediction ability in terms of mortality, there is a discrepancy within the results. We assume that this occurred because while other studies assessed patients at the time of admission, we conducted serial assessments, which improved diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 97%
“…17 The pSOFA score provided excellent discrimination of inhospital mortality in critically ill children with sepsis (AUC, 0.92; 95% CI, 0.91-0.94) and its performance was better than the other organ dysfunction scores and similar to PRISM III (AUC 0.88; 95% CI, 0.86-0.91), with a mortality rate of 12.1% in children with sepsis, and a mortality rate of 32.3% in children with septic shock. 30,31 A previous study demonstrated the ability of the pSOFA score to predict mortality in PICU patients with sepsis with a sensitivity of 83% (95% CI, 76-88%) and specificity of 72% (95% CI, 60-81%).…”
Section: Discussionmentioning
confidence: 99%
“…The findings led to the conclusion that pSOFA and PELOD2 scores serve as reliable predictors of mortality in critically ill children. Sun et al reported SOFA being superior to SIRS for predicting mortality in PICU patients with sepsis [ 12 ]. The pSOFA score, an age-adjusted pediatric version of the adult SOFA score, was adapted and validated by Matics et al and used it to evaluate the Sepsis-3 definitions in critically unwell children.…”
Section: Reviewmentioning
confidence: 99%